Tumbuka Prosody: Between Tone And Stress - Downing, Laura (My University, 2019)
Tumbuka is spoken in the northern Lake Malawi region where it is typical for Bantu languages to have what has been called a restricted tone system: all words must have a High tone. This kind of prosodic system has stress-like properties, and functions similar to Kisseberth & Odden (2003). Vail (1972) suggests that Tumbuka is a purely stress language. This paper argues, in contrast, that because Tumbuka High tone realization has tone-like properties, as defined in Hyman (2006; 2009; 2012; 2014), as well as stress-like properties, it cannot be considered a canonical stress language. It is proposed that the synchronic Tumbuka prosodic system evolved from one where contrastive High tone takes a phrasal domain through processes – formalizable as an OT factorial typology – which made phrasal prosody more transparently predictable by eliminating most tonal contrasts.
Keywords: Tumbuka prosody; Malawi; tone and stress